Vaccination against Q fever for biodefense and public health indications - Ruiz, Sara; Wolfe, Daniel N. (Frontiers in Microbiology, 2014)
Coxiella burnetii is the etiological agent of Q Fever, a disease that is often spread to humans via inhalational exposure to the bacteria from contaminated agricultural sources. Outbreaks have been observed all over the world with larger foci generating interest in vaccination programs, most notably in Australia and the Netherlands. Importantly, exposure rates among military personnel deployed to the Middle East can be relatively high as measured by seroconversion to C. burnetii-specific antibodies. Q Fever has been of interest to the biodefense community over the years due to its low infectious dose and environmental stability. Recent advances in cell-free growth and genetics of C. burnetii also make this organism easier to culture and manipulate. While there is a vaccine that is licensed for use in Australia, the combination of biodefense- and public health-related issues associated with Q Fever warrant the development of a safer and more effective vaccine against this disease.